The Integration of Artificial Intelligence in Apparel Fashion Industry: A Bibliometric Analysis - Adhikari, Ujjwal (Journal of Interdisciplinary Studies, 2026)
This research paper is an exploration on the use of artificial intelligence in the apparel textile industry. The keywords which were used to retrieve relevant documents included Textile, Fashion industry, Apparel and Artificial intelligence, relevant documents were downloaded in authentic online databases, which included Web of Science, and Scopus. The bibliometric analysis of peer-reviewed articles was conducted on 234 articles. Data merging, summarization, and visualization of a network were done with the help of tools like, Biblioshiny and VOSviewer. The results show great and increasing academic interest in this field. The number of authors for 234 articles was 732, which is an indicator of active research cooperation. China, Spain and Hong Kong are the top in terms of publication output and citation impact. Donghua University is the most fruitful institution having 127 publications in the data. The co-occurrence analysis keyword reveals that the most common and most closely related term is that of Artificial intelligence. Analysis of the sources reveals that the journal which has issued the most articles related to the topic is the Textile research journal (14), next are the International journal of clothing science and technology and journal of the textile institute. There are also high levels of international cooperation as evidenced in the area of network visualization. A critical analysis of the top ten most pertinent articles shows that artificial intelligence has evolved into an operational support solution to a strategic facilitator that improves creativity, decision-making, efficiency, and sustainability throughout the textile and fashion value chain. It is on this basis that a conceptual framework is suggested to direct future research. The research adds to the already existing debates about sustainable practices in the fashion industry and a basis to push the digital innovation forward to satisfy the increasing need in sustainable and customized products.